2012
DOI: 10.1556/jfc-d-12-00005
|View full text |Cite
|
Sign up to set email alerts
|

Diastereoselective [2+2] Photocycloaddition of a Chiral Cyclohexenone with Ethylene in a Continuous Flow Microcapillary Reactor

Abstract: The diastereoselective [2+2] photocycloaddition of ethylene to a chiral cyclohexenone was studied in a continuous flow microcapillary reactor. In all cases examined, the microcapillary reactor gave higher conversions and selectivity than the batch system, even after shorter irradiation times. These findings were explained by the superior temperature control, favorable light penetration, and generation of a gas-liquid slug flow with improved mass transfer in the microreactor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 32 publications
0
26
0
Order By: Relevance
“…It was shown that more effective photoirradiation derived from the short path length could be achieved in this area [8]. Similarly, Oelgemöller's group obtained thin solution films using O 2 gas as a reagent for a photoreaction [9], and Zhang's group reported that a thin liquid film was constructed by slug flow conditions using MeOH and oil and could be applied to synthesize biodiesel [16].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that more effective photoirradiation derived from the short path length could be achieved in this area [8]. Similarly, Oelgemöller's group obtained thin solution films using O 2 gas as a reagent for a photoreaction [9], and Zhang's group reported that a thin liquid film was constructed by slug flow conditions using MeOH and oil and could be applied to synthesize biodiesel [16].…”
Section: Resultsmentioning
confidence: 99%
“…Compared to batch processes, higher selectivity and productivity were achieved under these microflow conditions. In addition, heterogeneous [2+2] photoreactions using ethylene gas as a reagent in a microcapillary reactor was also reported, with high energy efficiency enabled by the two layers of ethylene gas and substrate solution that were formed [8]. Oelgemöller's group has also reported on the efficiency of photoreactions using slug flow involving a gaseous reagent and a solution [9].…”
Section: Introductionmentioning
confidence: 99%
“…In addition a small selection of aryl bromo substrates and heteroaryl iodides were tested but in general these failed to give good yields under the standardised conditions. 50b The method was used as part of the two-step telescoped process for the formation 107 The ethylene gas was delivered as a segmented flow stream through a FEP tube wrapped around a quartz immersion well with a 500 W medium pressure mercury lamp. The diastereomeric excess (d.e.)…”
Section: The Use Of Ethylene In Flowmentioning
confidence: 99%
“…A gas-liquid slug flow was also recently used for the [2 + 2] cycloaddition of a chiral cyclohexenone 89 with ethylene (Scheme 30) [83]. The reactor comprised of FEP tubing (1.0 mm i.d.)…”
Section: Reviewmentioning
confidence: 99%